Post a New Question

Algebra

posted by .

Solve the equation and check the solution:
-4(t+7)-(t+6)=10

the solution t is:

  • Algebra -

    - 4 ( t + 7 ) - ( t + 6 ) = 10

    - 4 * t - 4 * 7 - t -+ 6 = 10

    - 4 t - 28 - t - 6 = 10

    - 5 t - 34 = 10 Add 34 to both sides

    - 5 t - 34 + 34 = 10 + 34

    - 5 t = 44 divide both sides by - 5

    t = - 44 / 5 = - 8.8



    - 4 ( t + 7 ) - ( t + 6 ) = 10

    - 4 ( - 8.8 + 7 ) - ( - 8.8 + 6 ) = 10

    - 4 * ( - 1.8 ) - ( - 2.8 ) = 10

    7.2 + 2.8 = 10

    10 = 10

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question